Tuesday

July 22, 2014

July 22, 2014

Posted by **Mandy** on Wednesday, May 23, 2007 at 10:54am.

(X^2)/(X^2-16)=(5X+4)/(X^2-16)

I don't think it is finding the sum, but I can simplify the equation.

(X^2)/(X^2-16)=(5X+4)/(X^2-16)

First, multiply both sides by X^-16.

X^2 = 5X+4

Subtract 5X+4 from both sides.

X^2-5X-4 = 0

However, this equation cannot be factored. If the original equation was

(X^2)/(X^2-16)=(5X

Then it would simplfy to

X^2-5X+4 = 0

Which could be factored into

(X-1)(X-4) = 0

I hope this helps. Thanks for asking.

**Related Questions**

Find the sum - Can someone how to find the sum and simpliest form of this ...

calculus - 1) equation; sum= (1-(1+i)^-n / i 2) equation; sum= r(1+i)^-1 + r(1+i...

math - Find the two numbers that multiply to the product number and add to the ...

math - Q: Corbin is playing a board game that requires rolling two number cubes ...

probability - two fair six-sided dice are rolled and the sum of the dots on the ...

Reply to grant about a regression problem - This is a reply to the question ...

Precalculus - Find the sum of the first 50 terms of the sequence 2,4,6,8...

Algebra I - Hi, I would like someone to explain to me the process to get to the ...

calculus - find the sum of the series: 1. the sum from n=1 to infinity of ((-1)^...

Algebra - I have a few problems I need some help with. The first is Evaluate ...